Optimal Convergence Rates for Solutions of the Monopolar Non-Newtonian Flows - Zhi-qiang Luo (Abstract and Applied Analysis)
This paper is concerned with the optimal convergence rates for solutions of the monopolar non-Newtonian flows. By using the energy methods, the perturbed weak solution of perturbed system asymptotically converges to the solution of the original system with the optimal rates (1+t)-1/4.